Contrasting Effects of Wild Arachis Dehydrin Under Abiotic and Biotic Stresses - Mota, Ana Paula Zotta; Oliveira, Thais Nicolini; Vinson, Christina Cleo; Williams, Thomas Christopher Rhys; Costa, Marcos Mota do Carmo; Araujo, Ana Claudia Guerra; Danchin, Etienne G. J.; Grossi-de-Sá, Maria Fatima; Guimaraes, Patricia Messenberg; Brasileiro, Ana Cristina Miranda (Frontiers in Plant Science, 2019)
Plant dehydrins (DNHs) belong to the LEA (Late Embryogenesis Abundant) protein family and are involved in responses to multiple abiotic stresses. DHNs are classified into five subclasses according to the organization of three conserved motifs (K-; Y-; and S-segments). In the present study, the DHN protein family was characterized by molecular phylogeny, exon/intron organization, protein structure, and tissue-specificity expression in eight Fabaceae species. We identified 20 DHN genes, encompassing three (YnSKn, SKn, and Kn) subclasses sharing similar gene organization and protein structure. Two additional low conserved DHN -segments specific to the legume SKn-type of proteins were also found. The in silico expression patterns of DHN genes in four legume species (Arachis duranensis, A. ipaënsis, Glycine max, and Medicago truncatula) revealed that their tissue-specific regulation is associated with the presence or absence of the Y-segment. Indeed, DHN genes containing a Y-segment are mainly expressed in seeds, whereas those without the Y-segment are ubiquitously expressed. Further qRT-PCR analysis revealed that, amongst stress responsive dehydrins, a SKn-type DHN gene from A. duranensis (AdDHN1) showed opposite response to biotic and abiotic stress with a positive regulation under water deficit and negative regulation upon nematode infection. Furthermore, transgenic Arabidopsis lines overexpressing AdDHN1 displayed improved tolerance to multiple abiotic stresses (freezing and drought) but increased susceptibility to the biotrophic root-knot nematode Meloidogyne incognita. This contradictory role of AdDHN1 in responses to abiotic and biotic stresses was further investigated by qRT-PCR analysis using a set of stress-responsive genes involved in the abscisic acid and jasmonic acid signaling pathways in transgenic plants and suggested an involvement of DHN overexpression in these stress-signaling pathways.